Regulation of High-Affinity Iron Acquisition Homologues in the Tsetse Fly Symbiont Sodalis glossinidius - Runyen-Janecky, Laura J. (American Society for Microbiology (ASM), 2010)
Sodalis glossinidius is a facultative intracellular bacterium that is a secondary symbiont of the tsetse fly (Diptera: Glossinidae). Since studies with other facultative intracellular bacteria have shown that high-affinity iron acquisition genes are upregulated in vivo, we investigated the regulation of several Sodalis genes that encode putative iron acquisition systems. These genes, SG1538 (hemT) and SG1516 (sitA), are homologous to genes encoding periplasmic heme and iron/manganese transporters, respectively. hemT promoter- and sitA promoter-gfp fusions were constructed, and in both Escherichia coli and Sodalis backgrounds, expression levels of these fusions were higher when the bacteria were grown in iron-limiting media than when the bacteria were grown in iron-replete media. The Sodalis promoters were tested for iron regulation in an E. coli strain that lacks the fur gene, which encodes the iron-responsive transcriptional repressor Fur. Expression of the promoter-gfp fusions in the E. coli fur mutant was constitutively high in both iron-replete and iron-deplete media, and addition of either Shigella flexneri fur or Sodalis fur to a plasmid restored normal regulation. A Sodalis fur mutant was constructed by intron mutagenesis, and semiquantitative reverse transcription-PCR (RT-PCR) showed that iron repression of sitA expression was also abolished in this strain. In vivo expression analysis showed that hemT and sitA are expressed when Sodalis is within tsetse fly hosts, suggesting a biological role for these genes when Sodalis is within the tsetse fly.